PERAN PEMBELAJARAN BAHASA INDONESIA DALAM MEMBANGUN KARAKTER BANGSA DALAM KAJIAN AGAMA BUDDHA - S Sujiono (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
Brawls and drug abuse among students illustrate the not yet optimistic character ofthe nation. The research objective is to describe the role of Indonesian language learning inBuilding Nation Character in Buddhist studies. This type of research is a case study. The placeof this research is in Development Vocational School, Kec. Ampel, Kab. Boyolali. The time forconducting the study was August until December 2018. The results of the study found the role oflearning Indonesian in developing national character through the study of Buddhism. Studentsare conditioned to have the shame of doing evil (hiri) and fear of the consequences of doing evil(ottappa), religious attitudes by studying My Poetry, works of Taufiq Ismail, Nazam Life Poetry,Poetry Girl begging. Students are conditioned to think creatively in making short stories, analyzingnovels, analyzing gurimdam, making poems, making speeches. Students are conditioned to havea national spirit by analyzing short stories "Heroes of Captain Pattimura, short stories with thetheme of Heroes of Flowers Heroes. Students learn poetry and speeches about the love of thecountry. Students are taught friendship through Story 9 Fictions, and Laskar Pelangi Novel.